PENGARUH PENGEMBANGAN KARIR, MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN (KSP Prima Sejahtera Nganjuk) - Rindy Ani Nurcholippah; Sri Isnowati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to influence career development, work motivation and competence on the performance of KSP Prima Sejahtera employees. The type of research used for data collection is quantitative research with survey methods and distributing questionnaires. The population in this study includes all employees at KSP Prima Sejahtera Nganjuk as many as 93 people. The data analysis method used includes Instrument Test, namely Validity Test and Reliability Test, Multiple Linear Regression Analysis and Statistical Test, namely R2 Test, F Test and T Test. While the tools in this test use SPSS 25 Software. The results showed that career development had a significant positive effect on employee performance, motivation had a significant positive effect on employee performance, competence had a significant positive effect on employee performance, career development, motivation and competence had a significant positive effect on employee performance.